The Development of Effective Urban Farming Sales Method with Hydroponics Plantation System to Complete Instant Vegetable Supply in Urban Area - Pamuji, Wirawan; Dahliani, Lili; Jamaludin; Gorat, Ricki Rianto (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Urban Area Regency with limited land makes it difficult to plant with soil media; in this case the hydroponic media employees are intensifying the planting of water media. The Research applies Research and Development Methods for planting with Hydroponics to complete vegetable demands in Urban Areathat the planting media is not only done using soil but also with water media because in this case the employees can also provide a contribution to the Urban district government in carrying out Effective distribution of vegetable crops in an effective and high quality manner for subsequent marketing to meet adequate vegetable needs.